2017
DOI: 10.1007/s00259-017-3653-0
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT predicts survival after 90Y transarterial radioembolization in unresectable hepatocellular carcinoma

Abstract: Copyright: Blanc-Durand et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License 3.0 (CC BY 3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACT Purpose: To generate a predictive whole-liver radiomics scoring system for progression-free survival (PFS) and overall survival (OS) in patients undergoing transarterial radioembolization using Yttrium-90 (90 Y-TARE) for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…For patients treated with TARE using yttrium-90 ( 90 Y), contradictory results have been shown between studies. Previous studies have revealed longer progression-free survival and overall survival in patients with low FDG uptake of HCCs[72,74], including a recent prospective study with uniform patient cohort[75]. In contrast, one study showed no significant association between FDG uptake of HCCs and survival[73] and another study even showed better progression-free survival in patients with high FDG uptake[71].…”
Section: Fdg Uptake Of Hcc As a Predictor For Prognosismentioning
confidence: 99%
“…For patients treated with TARE using yttrium-90 ( 90 Y), contradictory results have been shown between studies. Previous studies have revealed longer progression-free survival and overall survival in patients with low FDG uptake of HCCs[72,74], including a recent prospective study with uniform patient cohort[75]. In contrast, one study showed no significant association between FDG uptake of HCCs and survival[73] and another study even showed better progression-free survival in patients with high FDG uptake[71].…”
Section: Fdg Uptake Of Hcc As a Predictor For Prognosismentioning
confidence: 99%
“…Accordingly, clinicians are interested in the ability of F‐FDG uptake in HCC to predict overall prognosis and response to TARE, as well as other treatments. Several studies have demonstrated that metabolic activity, assessed by PET/CT scan, can predict prognosis and treatment response including resection and external beam radiation therapy (EBRT) 24–26 . However, limited data are available regarding the predictive and prognostic values of FDG PET/CT after internal radiation treatments such as TARE.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have established the role of PET-CT in early prognostication and diagnosis of recurrent or residual disease in HCC. [56][57][58] A PET-based response assessment criteria known as Positron Emission Tomography Response Criteria in Solid Tumors (PERCIST) has also been proposed. 59 However, 18F-fluorodeoxyglucose (18F-FDG) is not specific for HCC and there is lack of data on the standardized uptake value (SUV) in predicting survival.…”
Section: Positron Emission Tomography (Pet)-ctmentioning
confidence: 99%